Survey of Traumatic Childbirth Experiences in Postpartum Mothers Using the City Birth Trauma Scale in Sorong Regency - Ahmar, Hamdiah; Andriany, Alia; Maharani, Rafika (Poltekkes Kemenkes Palu, 2024)
The mental health of postpartum mothers is influenced by traumatic childbirth experiences that can result in Post Traumatic Stress Disorder (PTSD). Individuals experiencing PTSD tend to be more sensitive. Poor mental health during the postpartum period can alter a woman's self-perception and disrupt family relationships. This research aims to conduct a Survey of Traumatic Childbirth Experiences in Postpartum Mothers Using the City Birth Trauma Scale in Sorong Regency. This is a quantitative survey research using the survey method to analyze risk factors for postpartum trauma incidents, employing the City Birth Trauma Scale 5 questionnaire by examining exposure or Odds Ratio (OR). Meanwhile, to test the validity and reliability of the Indonesian version of the City Birth Trauma Scale instrument, the Pearson Product-Moment Correlation and Cronbach's Alpha methods were used. The study was conducted in August-September 2023 at 2 Public Health Centers in Sorong Regency, Malawili Public Health Center, and Marian Public Health Center, with a sample of 70 postpartum mothers drawn using purposive sampling. The research results show that 24 respondents (100%) meet the diagnostic criteria for PTSD. Only 1 respondent (4%) does not meet the criteria for Non-Diagnostic PTSD. The conclusion of this research is that there is no significant relationship between the evaluated factors in the table and trauma symptoms, based on the analysis of the given P values and Odds Ratios (OR). Regular monitoring of postpartum mental health is necessary, especially for those experiencing early trauma symptoms.